Integrated farming system for livelihood security of small and marginal farmers in tribal area of Chhattisgarh - Jain, Vinamarta; Rajak, Krishnakant; Singh, S R K (Indian Farming, 2022)
Development of integrated farming system is very important as the system has multi-fold benefits to increase the income and wealth of farmers. Integrated farming systems would be a solution to overcome the problems that arise in the regional development. Underthe farmer FIRST Programme successful development of integrated farming system model in farmers’ field was done. At present, 14 farmers in adopted villages developed crops + vegetables + livestock based IFS model. The primary input for IFS model like crop and vegetable seeds, poultry and quail, goatry and fingerling, drip system and mulching etc. all component were provided under Farmer FIRST Programme. In this improved technology, tribal farmers were able to generate income round the year and also motivate other farmers to adopt IFS model. Further, in this system visible advantages include minimized risk and increased profitability as well as efficient integration of field crops with farm animals for sustainable production, income generation, and employment opportunities for resource-poor rural farm families.